Shipping, Tracking, And Returned Goods: The Determinants of Sustainable E-Commerce Supply Chain and Logistics Operation - Humairoh; Mohammad Annas (Jurnal Manajemen, 2023)
The main objectives of the research were to analyze many factors affecting the sustainability distribution, supply chain and logistic operation among e-commerce organization in Indonesia. The establishments were picked up randomly representing main regional in Indonesia. Ten e-commerce establishments were participating in the survey. 215 respondents representing nine e-commerce establishments gave their respond related on how they organized the shipping, tracking, handling as well as the returned goods policy. The result showed that the determinants were significantly gave impact on users’ satisfaction as well as the intention to repeat the business with the establishments, since in particular circumstances those ecommerce establishment gave hands on others to organize the goods shipping and distribution, and share the cost, so efficiency were created at both sides’ logistics operation.